Peran Sekolah Islam Terpadu Dalam Pembentukan Sikap, Moral Dan Akhlak Generasi Muda (Peran SD Swasta IT Petak Batuah) - Subroto, Wisnu; Maulana, Akhmad; Susanto, Heri (Lambung Mangkurat University, 2023)
Various cases of violence, harassment, abuse and other criminal cases are happening and are in the spotlight today. This happens because of the lack of attitude, moral and religious character education or character education. Seeing this situation, the existence of an Integrated Islamic School is one of the answers in guiding, educating and improving the character of children from an early age. This study aims to describe the role of IT Private SD Petak Batuah in the formation of attitudes, morals and morals of the younger generation. This study uses qualitative research methods that use data collection techniques through observation, interviews, and document studies. Data analysis uses descriptive qualitative analysis which includes the stages of reducing data, presenting data, and drawing conclusions. From the results of the study it can be concluded that the existence of the IT Petak Batuah Private Elementary School has played a role in shaping the attitudes, morals and morals of its students, where educational activities in schools are not only to educate children intellectually, but also to shape the personality and character of students as a whole, described in several ways. as follows: 1) The implementation of school education combines general education with Islamic education, seen in educational activities that are in the packaging of Islamic teachings and values. 2) There are religious activities designed to shape the character of students which include routine habituation activities every day as well as activities on certain days which include; dhuha prayer in congregation, additional hours, yasin tahlil, and watching together one day. 3) schools shape the personality of students through the example that educators do in their various activities, becoming real examples in various words and actions that are seen by students.